Improving lost-wax casting with six sigma methodology - W. Laosiritaworn (2018)
© 2015 Taylor & Francis Group, London. This research describes an application of Six Sigma Methodology to improve lost-wax casting. Lost-wax casting is one of the most important production processes in the case study of a company which is a manufacturer of factory automation products. Production is labour intensive with non-standardized instructions, leading to a high defect rate. Broken and leaking molds are the most common defects. Six Sigma’s DMAIC (Define-Measure-Analyze-Improve-Control) methodology was used to identify and analyze the sources of variation in production. Poor mold assembly and ceramic coating were identified as mostly responsible for the mold defects. Based on this analysis, the production process was improved and instructions were standardized, reducing the defect rate.